THE ROLE OF SENSORY DESIGN AS A TOOL FOR SCHOOL INCLUSION OF CHILDREN WITH ASD - Silva, Jammylly Fonseca (LUMEN ET VIRTUS, 2023)
Sensory-friendly environments play a crucial role in enhancing the educational experience for individuals with Autism Spectrum Disorder (ASD). These environments are carefully designed to accommodate sensory sensitivities, which, if not addressed, can create barriers to learning and social interaction. This paper explores how sensory design elements such as acoustics, visual stimuli, tactile experiences, olfactory considerations, and spatial organization can positively impact students with ASD, promoting inclusivity and improving their ability to engage in educational settings. Acoustic design, such as sound-absorbing materials, is essential in reducing sensory overload caused by everyday sounds, which can be distressing for individuals on the autism spectrum. Visual harmony, achieved through soft lighting and calming color palettes, helps reduce anxiety and create a peaceful atmosphere conducive to focus. Tactile considerations, including the use of diverse textures, provide sensory exploration opportunities while ensuring comfort. Olfactory sensitivity, often overlooked, can be addressed by establishing fragrance-free zones or using calming scents like lavender. Finally, spatial organization plays a significant role in creating a sense of security, as both overly open and overly confined spaces can be overwhelming. By integrating these sensory-friendly design principles into educational environments, schools can create spaces where students with ASD feel comfortable and supported. This paper highlights the importance of designing environments that respect individual sensory needs and demonstrates how thoughtful modifications can enhance participation, focus, and overall well-being. The Sensory Room at the Harkin Institute serves as a model for these principles, offering a customizable environment that adapts to the needs of its visitors. Ultimately, this approach to sensory design promotes a more inclusive and equitable educational experience for children with ASD, ensuring they can fully engage in their learning environment.